The Effectiveness of Movie for the Enhancement of Students' Vocabulary - Ditha Kusumarajni (Journal Corner of Education, Linguistics, and Literature, 2022)
This research is used to find out whether there is any improvement of students’ vocabulary after they are taught using movie. A one group pretest and posttest design was used in this research. The data were collected from a pre-test and a post-test.  The research was conducted at SMAN 1 Way Jepara Lampung Timur with the subjects were the first grades students. The result showed that there is a significant improvement in students’ vocabulary mastery after that students had been taught by using movie. The second finding reveals that nouns was the type which improved the most after the students had been taught through movie. This indicates that movie can be used to facilitate the students to improve their vocabulary.